Desain dan Pembuatan Prototype Piston Honda MEGAPRO FI Menggunakan 3D Printing - Frince Marbun; Richard A M Napitupulu (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2020)
3D printing technology has great potential in today's manufacturing world, one of its uses is in making miniatures or prototypes of a product such as a piston. One of the most famous and inexpensive 3D printing (additive manufacturing) technologies is Fused Deposition Modeling (FDM), the principle FDM works by thermoplastic extrusion through a hot nozzle at melting temperature then the product is made layer by layer. The two most commonly used materials are ABS and PLA so it is very important to know the accuracy of product dimensions. FDM 3D Printing Technology is able to make duplicate products accurately using PLA material. FDM machines work by printing parts that have been designed by computer-aided design (CAD) and then exported in the form of STL or .stl files and uploaded to the slicer program to govern the printing press according to the design. Using Anet A8 brand 3D printing tools that are available to the public, Slicing of general CAD geometry files such as autocad and solidwork is the basis for making this object. This software is very important to facilitate the design process to be printed. Some examples of software that can be downloaded and used free of charge such as Repetier-Host and Cura. by changing the parameters in the slicer software is very influential in the 3D printing manufacturing process.